PELESTARIAN ALAM DALAM ARSITEKTUR : MASALAH DAN USULAN PEMECAHANNYA - Murni Rachmawati; JosefThis study concern to discuss about Prijotomo (Bumi Lestari Journal of Environment, 2010)
As a built environment, architecture had faced the challenges that must be answered in 21st century. The most ever whelmingly urgent crisis facing mankind is the degradation of the natural environment. The fragility of the natural environment comes to the fore as a compelling principle for the revitalization of architecture. This study intended to formulate theory or principle that leads architecture to faced the challenge. This is a library research, with logical argumentation & critical methods and Jurgen Habermas strategy. The result hope to be a theoretical alternative in architecture, especially for revitalization in nature and architecture.